Lines of Thought 1983-2015 - Derrick Grisanti, Paul Scott (Biblioteca Javier Coy d'estudis Nord-Americans, 2016)
This book brings together twelve essays published between 1983 and 2015. They reveal the author's continuing interest in what is argued here to be the central, although subversive and recessive line of thinking in American and western society. This romantic thread is followed mainly from Ralph Waldo Emerson through Emily Dickinson to Martin Heidegger and Stanley Cavell. Este libro reúne doce ensayos publicados entre 1983 y 2015, que revelan el continuo interés del autor en lo que se argumenta aquí como la línea de pensamiento central, aunque subversiva y no dominante, de la sociedad americana y occidental. Este hilo romántico es seguido principalmente desde Ralph Waldo Emerson hasta Martin Heidegger y Stanley Cavell, pasando por Emily Dickinson.